Effects of Occupational Therapy Program Based on Active Meditation on Hair Cortisol Levels in Undergraduate Healthcare Students - Espinosa, Alejandra (2022)
Context. Meditation incorporation helps to fight against disorders such as depression, stress, and anxiety. Specifically, few studies have studied Osho's Active Meditation on young people, but observed evidence using passive meditation shows that it could improve stress well-management, emotional control, and other mental unhealthy conditions. Goal. The present study pointed to evaluate the results of an occupational therapy program centered on active meditation on hair cortisol concentration in a sample of undergraduate healthcare students. Methods. Undergraduate students from the University of Chile's health careers were divided at random into control (n=7) and treated groups (n=15). The treated group participated in an active meditation program once a week for three months. This treatment included different techniques such as Chakra Sounds, Nataraj, Mandala, Kundalini, Devavani, Gourishankar, and Nadabrahma. Hair samples were taken before and after the treatment period to measure cortisol. Results. The control group increased cortisol level 168.9±76.8 pg/mg compared with initial levels. The treated group shows a decrease of initial cortisol values in 28.5±12.8 pg/mg after meditation protocol application. Conclusions. Blending active meditation in students' daily routine through occupational therapy intervention might prevent undergraduate students' stress in healthcare careers.